IMPACT OF AHARAJA AND VIHARAJA NIDAN IN PANDU W.S.R. TO DIETARY AND LIFE STYLE FACTORS IN ANAEMIA (International Journal of Ayurveda and Pharma Research, 2020)
Anaemia is an extremely prevalent condition common in all human of all ages, living in all condition and continents. It has got serious consequences for both the human health as well as the socioeconomic status of the country). Globally, 50% of anemia is attributable to iron deficiency and accounts for approximately 841,000 deaths annually worldwide. According to Ayurveda as well as in modern system of medicine has accepted that Aharaja nidan (diet & regimen) and Viharaja (lifestyle factors) are plays an important role in pathogenesis of Pandu (anaemia). The aim of the study was to identify those factors among the age group 10 to 60 years and to create the awareness to the community in the future. A cross sectional survey study was conducted in 120 patients of Pandu attending the OPD & IPD of Shyamadas Vaidya shastra pith hospital in Kolkata West Bengal, irrespective of their sex, religions & economic status through collecting data by questionnaires and they have been observed on dietary, physical, and psychological factors. The obtaining data revealed that especially female participants, rural as well as urban people, people from low & middle economic status were suffering from Pandu due to inadequate, improper intake of Aharaja & Viraja nidan.  After evaluation of these factors, it can be concluded that, Aharaja & Viharaja nidan had been justified in the pathogenesis of Pandu which was depicted in different Ayurvedic compendium & about the scenario of Nidan in this particular population were suffering from Pandu.